AVO analysis in gas hydrate exploration and the possibility of its application in deep water continental shelf of Vietnam - Huyen, Nguyen Thu; Hieu, Nguyen Trung; Cuong, Tong Duy; Hung, Nguyen Manh; Lam, Nguyen Danh; Cuong, Trinh Xuan (Petrovietnam Journal, 2015)
AVO, which stands for Amplitude Variation with Off set - or more simply, Amplitude Versus Off set, is a seismic technique that looks for direct hydrocarbon indicators using amplitudes of prestack seismic data. The AVO technique became very popular in the petroleum industry, as one could physically explain the seismic amplitudes in terms of rock properties. For example, bright-spot anomalies (i.e. the high amplitude refl ections seen on the P-wave stacked section) could be investigated before stack to see if they also had AVO anomalies. It can help us distinguish the geological objects that created bright-spot anomalies, such as gas-bearing sandstones, coal seams or volcanoes. AVO analysis proved successful in certain areas of the world for gas hydrate exploration but has not been applied in Vietnam. In this paper, the authors describe AVO analysis methods and some examples of using AVO in gas hydrate exploration in the world as well as the possibility to apply it in deep water areas on the continental shelf of Vietnam.